DEMOGRAPHIC IMPACTS OF SECURITY CHALLENGES IN NIGERIA: A QUALITATIVE PERSPECTIVE - Olaosebikan, Johnson Sogo; Olodude, Opeyemi Dorcas; Atoyebi, Timothy Abayomi; Sunmola, Kazeem Adebayo; Olaifa, Oluwafemi James (African Journal of Social and Behavioural Sciences, 2025)
There is a growing concern among citizens about widespread insecurity in Nigeria. This study examined the demographic impacts of security challenges in Nigeria. The study is qualitative in nature and adopted desk review of published and scholarly articles. Relevant articles were extracted using Google Scholar and Research Rabbit platforms to filter relevant articles using keywords such as demographic implications, demographic impact, demographic effects, insecurity, armed conflict, armed struggles, security challenges and Nigeria. The study showed that ethnic and religious divisions, political instability, economic factors, and perceived marginalisation of sections of the country were causes of insecurity in the country. Other causes were corruption, youth unemployment, desire for secession, mass poverty and competition for resources especially between herders and farmers. The study further highlighted the demographic consequences of insecurity to be displacement of population and increase in internally displaced persons, recruitment of children as kid-soldiers, children not having access to education and healthcare, alteration in population dynamics of the conflict areas because of increased ill health, death and migration. Moreover, security challenges often lead to the loss of jobs and livelihoods in the conflict areas. The study concluded that to improve the security of the country, the government should provide employment opportunities for the unemployed youths, overhaul security apparatus, and employ, train and improve the welfare of security personnel to boost their morale. In addition, the government should collaborate with other countries to fight insurgences to reduce the influx of criminals across national boundaries. The government should prioritise the protection of citizens by ensuring that modern equipment needed by security forces is procured to combat criminals. The government should provide grazing reserves for animal rearing instead of allowing herders to roam their animals across the country. Also, criminals caught should be made to face the full wrath of the law to serve as a deterrent to others. The study expands the frontier of knowledge in the area of migration, conflict investigation, and development, creating a treasured addition to both academic and policy debates.